An Efficient Carbon‐Based Drug Delivery System for Cancer Therapy through the Nucleus Targeting and Mitochondria Mediated Apoptotic Pathway. Issue 12 (16th November 2021) - Zhang, Junfeng; Li, Chenchen; Xue, Qianghua; Yin, Xuelian; Li, Yajie; He, Wen; Chen, Xuerui; Zhang, Jian; Reis, Rui L.; Wang, Yanli
Abstract: The emergence of nanocarriers solves the problems of antitumor drugs such as non‐targeting, huge side effects, etc., and has been widely used in tumor therapy. Some kinds of antitumor drugs such as doxorubicin (DOX) mainly act on the nucleic acid causing DNA damage, interfering with transcription, and thereby disrupting or blocking the process of cancer cell replication. Herein, a new nanodrug delivery system, the carbon‐based nanomaterials (CBNs)‐Pluronic F127‐DOX (CPD), is designed by using CBNs as a nanocarrier for DOX. As a result, the tumor growth inhibition rate of CPD group is as high as 79.42 ± 2.83%, and greatly reduces the side effects. The targeting rate of the CPD group of DOX in the tumor nucleus is 36.78%, and the %ID/g in tumor tissue is 30.09%. The CPD regulates the expression levels of Caspase‐3, p53, and Bcl‐2 genes by increasing intracellular reactive oxygen species (ROS) levels and reducing mitochondrial membrane potential, which indicates that mitochondrial‐mediated pathways are involved in apoptosis. The CPD nanodrug delivery system increases the effective accumulation of DOX in tumor cell nuclei and tumor tissues, and generates massive ROS, thereby inhibiting tumor growth in vivo, representing a promising agent for anticancer applications. Abstract : The carbon‐based nanomaterials‐Pluronic F127‐DOX (CPD) can increase the effective accumulation of doxorubicin (DOX) in tumor cell nuclei and tumor tissues. In addition, CPD increases the level of intracellular reactive oxygen species, reduces mitochondrial membrane potential, and regulates the expression levels of Caspase‐3, p53 and Bcl‐2 genes, suggesting that mitochondrial mediated pathways involved in apoptosis induced by CPD.